Energy absorption for crashworthiness in carbon-fibre braided composite structures - Lazarus, Simon David (Cranfield University, 2004)
In this investigation the effects of material, structural and testing parameters of carbon epoxy braided composite tubes were analysed with respect to their performance in crush and impact conditions. An original method of manufacturing the composite tubes with vacuum infusion together with an expandable foam core to form multi-cellular structures was used. Low cost, 24k tow carbon fibre braids were used and their performance was compared with that of the more expensive l2k tow size fibres. The specimens produced were axially crushed at constant quasi-static low velocities and at higher impact velocities using an instrumented falling weight machine. Load displacement data gathered from such tests were used to evaluate the test specimens with respect to their specific energy absorption values. The effects of a number of parameters including fibre tow size, braid architecture, resin content and loading type were evaluated. From the experimental results analysed from the test specimens it can be concluded that: - The 24k fibre showed lower specific energy absorption values than specimens made from l2k fibre. Epoxy resin content rather than epoxy resin type can significantly affect the specific energy absorption values. In general, specimens tested in impact loading exhibited lower specific energy absorption values than the same specimens test in quasi-static crush. A reasonably good correlation between global density and specific energy absorption for the type of structures examined was found
Keywords: Crush; Impact; Coretex